2019
DOI: 10.1080/1343943x.2019.1667834
|View full text |Cite
|
Sign up to set email alerts
|

Multidisciplinary assessment of agricultural innovation and its impact: a case study of lowland rice variety WITA 9 in Côte d’Ivoire

Abstract: Information on comprehensive evaluation of agricultural innovations is often limited. This study provides an overview of multidisciplinary evaluation of a lowland rice variety, WITA 9 (released in Côte d'Ivoire in 1998), with respect to its agronomic performance, grain quality, resistance to diseases, adoption by farmers, impact on productivity and farmers' income, and marketability. WITA 9 had the highest paddy yield among the tested varieties including an international check (IR 64) and recently developed va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 49 publications
0
12
0
Order By: Relevance
“…What are the yield and area growth rates required to achieve rice self-sufficiency in SSA by the target date of the Sustainable Development Goals (SDGs) in 2030? Although the impact of technologies is frequently discussed in the literature ( Arouna et al, 2017 , Jiao and Schneeberger, 2017 , Kassie et al, 2011 , Saito et al, 2019 ), the impact assessment of policy measures is limited, and to the best of our knowledge, this is the first attempt to estimate the impact of the CARD framework. In addition, while extensive literature exists on the separate application of the autoregressive integrated moving average (ARIMA) model ( Ruby-Figueroa et al, 2017 , Sen et al, 2016 ) and counterfactual approach ( Arouna et al, 2017 , Manda et al, 2019 ), the combination of the two methods to assess the impact of policy is uncommon.…”
Section: Introductionmentioning
confidence: 99%
“…What are the yield and area growth rates required to achieve rice self-sufficiency in SSA by the target date of the Sustainable Development Goals (SDGs) in 2030? Although the impact of technologies is frequently discussed in the literature ( Arouna et al, 2017 , Jiao and Schneeberger, 2017 , Kassie et al, 2011 , Saito et al, 2019 ), the impact assessment of policy measures is limited, and to the best of our knowledge, this is the first attempt to estimate the impact of the CARD framework. In addition, while extensive literature exists on the separate application of the autoregressive integrated moving average (ARIMA) model ( Ruby-Figueroa et al, 2017 , Sen et al, 2016 ) and counterfactual approach ( Arouna et al, 2017 , Manda et al, 2019 ), the combination of the two methods to assess the impact of policy is uncommon.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, local paddy rice production must significantly increase in order to meet the increased rice demand for consumption. Côte d'Ivoire's paddy rice production is based on two production systems: the highland rice system (upland rice) and the lowland rice system (flooded rice and irrigated rice) accounted for 72% and 28% of the total rice area, respectively, in 2016 [3]. In upland rice farming (URF), rice is cultivated without soil surface flooding.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of yields per hectare, a relevant number of studies carried out in the country have shown that the paddy rice productivity at the farm-level is still low in Côte d'Ivoire [1][2][3][4][5]. The national paddy yield is 2.3 t ha −1 for all paddy rice production systems combined [3], while the average yields per hectare in some sub-region countries such as Mali range from 5.6 t ha −1 to 6.7 t ha −1 [6]. Although paddy rice production increases over the years, this increase is less proportional than the area cultivated.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations